The impact of sound stimulations during pregnancy on fetal learning: a systematic review - Kobra Movalled; Anis Sani; Leila Nikniaz; Morteza Ghojazadeh (BMC, 2023)
Abstract Background The developing nervous system in utero is exposed to various stimuli with effects that may be carried forward to the neonatal period. This study aims to investigate the effects of sound stimulation (music and speech) on fetal memory and learning, which was assessed later in neonatal period. Methods The MEDLINE (pubmed), Scopus, EMBASE, and Cochrane Library were searched. Two reviewers selected the studies and extracted the data independently. The quality of eligible studies was assessed using The Joanna Briggs Institute Critical Appraisal Checklist for Randomized Controlled Trials (RCTs). Results Overall 3930 articles were retrieved and eight studies met the inclusion criteria. All of the included studies had good general quality; however, high risk of selection and detection bias was detected in most of them. Fetal learning was examined through neonatal electrocardiography (ECG), electroencephalography (EEG), habituation tests, and behavioral responses. Seven studies showed that the infants had learned the fetal sound stimulus and one study indicated that the prenatally stimulated infants performed significantly better on a neonatal behavior test. There was considerable diversity among studies in terms of sound stimulation type, characteristics (intensity and frequency), and duration, as well as outcome assessment methods. Conclusions Prenatal sound stimulation including music and speech can form stimulus-specific memory traces during fetal period and effect neonatal neural system. Further studies with precisely designed methodologies that follow safety recommendations, are needed. Graphical Abstract